THE VIDEO-BODY AND NARRATIVES OF THE SAME AND THE OTHER: VIDEOBODY (Palíndromo, 2018)
We present this article on the narratives of oneself and the other through the study of the video Entre de Nina Galanternick. Starting from the argument that the body that performs for the camera acts as a sense operator of the videographic device and that syncretism body-machine acts as the protagonist of the construction of identity between the subjects, we seek to bring the video of the ideas of programming and device, to defend it as a performance element, as well as a means of registration or documentation. For theoretical reasons we chose the authors Gilles Deleuze, Giorgio Agamben and Vilém Flusser and their studies on devices and techno-images, Hans Belting and the relationship between body and image and Arlindo Machado and the art of Brazilian video. Knowing the relationships between visibility and interaction, body and video, performance art and videographic language allowed us to understand how to construct the meaning of life, relationships between bodies and the narratives of oneself and the other.
Keywords: body; videoperformance; videographic device; Nina Galanternick